Root biomechanical properties of Chrysopogon zizanioides and Chrysopogon nemoralis for soil reinforcement and slope stabilisation - Trung Nghia Phan; Suched Likitlersuang; Viroon Kamchoom; Anthony Kwan Leung (My University, 2021)
Abstract Plant root reinforcement in soil bioengineering has gained increasing interest as a means of sustainable and environmentally friendly soil reinforcement and stabilisation. While Chrysopogon zizanioides is widely distributed in tropical regions worldwide and has been advocated for use in slope stabilisation and soil erosion control, C . nemoralis is normally distributed in mountainous areas in Southeast Asian countries, and its potential to reinforce soil has rarely been explored in the soil bioengineering literature. With the importance of root properties in soil bioengineering, this study was carried out to provide a comprehensive dataset of root biomechanical properties, morphological traits, and root reinforcement of these two contrasting vetiver species. A series of experiments, including root observation with a rhizobox system, uniaxial tensile test, and direct shear test, was performed. Results showed that Young's modulus and diameter of C . nemoralis roots were almost 1.4‐ and 1.3‐times greater than those of C . zizanioides roots ( p < 0.05). By contrast, no significant difference between the two vetiver species was observed in terms of tensile strength, 'side' root area ratio (RAR S ), and root orientation ( p > 0.05). The diameter–strength ( R 2 = 0.55–0.56, p < 0.05) and diameter–modulus relationships ( R 2 = 0.51–0.6, p < 0.05) of both species were consistent with negative power‐law models. Conversely, their diameter–orientation relationship followed a linear model ( R 2 = 0.85–0.89; p > 0.05). The soil shear strength in terms of cohesion greatly increased in the presence of the roots of C . nemoralis (Δ c = 4.9 kPa) and C . zizanioides (Δ c = 4.4 kPa). Therefore, C . nemoralis could be an alternative to C . zizanioides in soil bioengineering applications.
Keywords: Plant roots; Cohesion (chemistry); Tree Root and Stability Studies